Applying the United Kingdom Comparative Assessment Process to Decision Making for the Decommissioning of California OCS Platforms (Global Journal of Science Frontier Research, 2023)
This paper reviews the legal and regulatory regime for decommissioning oil and gas platforms on the United Kingdom Continental Shelf UKCS and in the North Sea and the process followed by UK regulatory authorities in approving an exception derogation to the requirement to fully remove all structures This exception allows the footings i e the lower base section of the jacket structure of large steel jacketed platforms to remain in-situ The paper provides details on how UK Platform Ninian North Ninian was removed and the Comparative Assessment of decommissioning options prepared by the owners of the platform that supported the decision by UK regulatory authorities to allow the jacket footings to remain in-situ The paper notes that the U S Outer Continental Shelf OCS Oil and Gas Regulations allow partial removal of platform jackets under some circumstances and that there are eight California oil and gas platforms which have jackets that would qualify for partial removal i e derogation based on the criteria established for North Sea oil and gas installations To obtain permit approvals from federal and state regulatory agencies to leave the lower portions of largeCalifornia platform jackets in-situ the owners of the platforms will need to clearly demonstrate partially removing the jackets is the best overall optimum decommissioning option This can be demonstratedby preparing Comparative Assessmentswhich evaluate platform decommissioning options using safety technical environmental and economic cost criteria